2020
DOI: 10.1186/s12885-020-07101-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastasis by tumor-infiltrating lymphocytes in T1 breast cancer

Abstract: Background: Lymph node metastasis is more likely in early-stage breast cancer with lower tumor-infiltrating lymphocyte (TIL) density. Therefore, we investigated the correlation between TILs and lymph node metastasis in cT1 breast cancer patients undergoing surgery and the usefulness of TILs in predicting sentinel lymph node metastasis (SLNM) in cT1N0M0 breast cancer. Methods: We investigated 332 breast cancer patients who underwent surgery as the first-line treatment after preoperative diagnosis of cT1. A posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
4
19
1
1
Order By: Relevance
“…In this study, TILs were suggested to possibly be a distant metastatic predictor, although not an independent factor. We have reported that TILs may also be involved in lymph node metastasis in HR + HER2 − BC [51]. In this study, TILs were considered to be strongly correlated with lymph node metastasis, being involved in distant metastasis prediction as well as prognosis after recurrence.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, TILs were suggested to possibly be a distant metastatic predictor, although not an independent factor. We have reported that TILs may also be involved in lymph node metastasis in HR + HER2 − BC [51]. In this study, TILs were considered to be strongly correlated with lymph node metastasis, being involved in distant metastasis prediction as well as prognosis after recurrence.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, TIL density was suggested to possibly be a distant metastatic predictor, although not an independent factor. We previously reported that TILs may also be involved in lymph node metastasis in HR+/HER2-breast cancer [52]. In this study, TILs were considered to be strongly correlated with lymph node metastasis, and were involved in distant metastasis prediction as well as prognosis after recurrence.…”
Section: Discussionmentioning
confidence: 89%
“…An increasing number of studies have shown that tumor-infiltrating lymphocytes can be used as related indicators to predict tumor metastasis and invasion [ 36 , 37 ]. Therefore, by analyzing the TIMER database, we found a correlation between the expression levels of the members of the EGFR family and the level of immune infiltration in glioma tissues.…”
Section: Resultsmentioning
confidence: 99%